Aspiration-Induced Acute Lung Injury in Victims with Isolated Severe Brain Injury - Yu. A. Gorodovikova; V. V. Moroz; A. M Golubev; Yu. V. Marchenkov; Yu. A. Churlyaev (Общая реаниматология)
Objective: to determine the time and development rate of acute lung injury (ALI) in severe brain injury (SBI) complicated by aspiration of gastric contents or blood. Subjects and methods. Twenty-nine patients aged 19 to 70 years, who had isolated SBI, of whom there were 24 males and 5 females), were examined. The patients were divided into 2 groups: those with aspiration of gastric contents (n=9) or blood (n=10). A control group included 10 patients with SBI without aspiration. A PiCCO plus device was used to determine pulmonary extravascular fluid. ALI was diagnosed in accordance with the recommendations of the Research Institute of General Reanimatology, Russian Academy of Medical Sciences. Results. SBI patients with aspiration of gastric contents or blood were found to have significantly increased pulmonary extravascular water (p<0.01) and a lower oxygenation index (<300), which correlated with each other. ALI was recorded in the first hours after injury in about 50% of cases in both patients with gastric contents aspiration and those with blood aspiration. Conclusion. In patients with SBI complicated by aspiration of gastric contents or blood, pulmonary extravascular fluid accumulation concurrent with other signs of injury may be regarded as a criterion for acute lung injury. Key words: severe brain injury, aspiration, acute lung lesion.